Ear wax and otitis media in children. Issue 6492 (10th August 1985) - Fairey, A; Freer, C B; Machin, D
Abstract : A study was designed to find the prevalence of ear wax in children aged 3 to 10 years and to test the belief that large amounts of wax are unlikely to be seen when otitis media is present. Roughly a quarter of the children had appreciable amounts of wax, and there was a gradual decline in prevalence with age. The amount of ear wax appeared to decrease when otitis media was present. The results did not support removing wax when assessing children's ears in general practice.